Harmful cyanobacteria-diatom/dinoflagellate blooms and their cyanotoxins in freshwaters: A nonnegligible chronic health and ecological hazard. (15th April 2023) - Zhang, Yanyan; Whalen, Joann K.; Cai, Chen; Shan, Kun; Zhou, Hongxu
Highlights: Cyanobacteria, diatoms and dinoflagellates blooms can synthesize cyanotoxins. The successive presence of cyanotoxins may pose chronic toxicity. Abiotic-biotic factors that affected seasonal shifts of algal species were documented. Multiple ecological roles and physiological functions of cyanotoxins were evaluated. Human and ecological health risks of harmful algal blooms were illustrated. Abstract: Human and ecological health depends on the vitality of freshwater systems, but these are increasingly threatened by cyanotoxins released from harmful algal blooms (HABs). Periodic cyanotoxin production, although undesirable, may be tolerable when there is enough time for cyanotoxins to degrade and dissipate in the environment, but the year-round presence of these toxins will be a chronic health for humans and ecosystems. The purpose of this critical review is to document the seasonal shifts of algal species and their ecophysiological acclimatation to dynamic environmental conditions. We discuss how these conditions will create successive occurrences of algal blooms and the release of cyanotoxins into freshwater. We first review the most common cyanotoxins, and evaluate the multiple ecological roles and physiological functions of these toxins for algae. Then, the annual recurring patterns HABs are considered in the context of global change, which demonstrates the capacity for algal blooms to shift from seasonal to year-round growth regimes that are driven by abiotic and biotic factors, leading to chronic loading of freshwaters with cyanotoxins. At last, we illustrate the impacts of HABs on the environment by compiling four health issues and four ecology issues emanating from their presence in the that covers atmosphere, aquatic ecosystems and terrestrial ecosystems. Our study highlights the annual patterns of algal blooms, and proposes that a "perfect storm" of events is lurking that will cause the 'seasonal toxicity' to become a full-blown, 'chronic toxicity' in the context of the deterioration of HABs, highlighting a non-negligible chronic health and ecological hazard. Graphical abstract: Image, graphical abstract